2017
DOI: 10.3892/etm.2017.5201
|View full text |Cite
|
Sign up to set email alerts
|

CHAF1A, the largest subunit of the chromatin assembly factor?1 complex, regulates the growth of H1299 human non‑small cell lung cancer cells by inducing G0/G1 cell cycle arrest

Abstract: Chromatin assembly factor 1 subunit A (CHAF1A) is the largest subunit of the chromatin assembly factor 1 (CAF-1) complex that is implicated in the assembly of nucleosomes on newly synthesized DNA. The aim of the present study was to determine its expression and biological function in non-small cell lung cancer (NSCLC). The current study examined the levels of CHAF1A expression in 22 samples of NSCLC and corresponding normal lung tissues. Subsequently, endogenous CHAF1A expression in H1299 NSCLC cells was knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In addition, CHAF1A was predicted as a putative target gene of miR-1179 using TargetScan website, and miR-1179 mimic significantly reduced the mRNA and protein level of CHAF1A. CHAF1A is the main functional subunit of CHAF1 protein (Liu et al, 2017), which is involved in deoxyribonucleic acid (DNA) replication, gene expression regulation and DNA mismatch repair (Cai et al, 2018). It was found that CHAF1A plays an essential role in the occurrence and development of various malignant tumors, and is related to a poor prognosis of cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CHAF1A was predicted as a putative target gene of miR-1179 using TargetScan website, and miR-1179 mimic significantly reduced the mRNA and protein level of CHAF1A. CHAF1A is the main functional subunit of CHAF1 protein (Liu et al, 2017), which is involved in deoxyribonucleic acid (DNA) replication, gene expression regulation and DNA mismatch repair (Cai et al, 2018). It was found that CHAF1A plays an essential role in the occurrence and development of various malignant tumors, and is related to a poor prognosis of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Primers for miR-1179, snRNA U6, β-actin, ZEB1 and CHAF1A were synthesized by Sangon Biotech (Shanghai, China). Primers were as follows: ZEB1 (Peña et al, 2006): forward primer: 5'-GC-CAATAAGCAAACGATTCTG-3' and reverse primer: 5'-TTTGGCTGGATCACTTTCAAG-3'; miR-1179: forward primer: 5'-GGCTGGAAAGGAAGAAG-3'; reverse primer: 5′-GTTAACCCGGCGGTGA-3′; CHAF1A (Liu et al, 2017): forward primer: 5'-AGGGAAGGT-GCCTATGGTG-3' and reverse primer: 5'-CAGG-GACGAATGGCTGAGTA-3'; U6: forward primer: 5'-CTCGCTTCGGCA GCACA-3' and reverse primer: 5'-AACGCTTCACGAATTTGCGT-3'; β-actin : forward primer: 5'-GAGCTACGAGCTGCCT-GACG-3' and reverse primer: 5'-GTAGTTTCGTG-GATGCCACAG-3'. The qPCR data were analyzed by comparative Ct method and 2 −ΔΔCT method.…”
Section: Cell Transfectionmentioning
confidence: 99%
“…Meanwhile, studies concerning the relationship between CHAF1A and clinical pathology have shown that CHAF1A represents a predictor of poor prognosis of breast cancer [9], colon cancer [10], glioblastomas [12], tongue squamous cell carcinoma [15] and gastric cancer [18]. Based on the study with expanded NSCLC case numbers by Liu et al [19], the high protein expression of CHAF1A was verified in these NSCLC cases. Higher CHAF1A expression was related to the shortened overall survival and diseasefree survival periods of NSCLC.…”
Section: Chaf1a Knock-down Inhibits Proliferation Of Lung Cancer Cellsmentioning
confidence: 97%
“…CHAF1A knock-down can inhibit the proliferation of lung cancer cell lines, induce cellular apoptosis and reduce cell clone formation. However, in the cell cycle experiment, to avoid the poor growth status of cells in the absence of serum, 5% fetal bovine serum was added to the culture solution herein, which may have led to the observed differences in the number of cells that entered S-phase when compared with the Liu et al [19] study. The mechanism underlying the proliferation-inducing effects of CHAF1A on the H1299 cells is still unknown, which might be related to miR-520b.…”
Section: Chaf1a Knock-down Inhibits Proliferation Of Lung Cancer Cellsmentioning
confidence: 97%
See 1 more Smart Citation